An Empirical Study of Email-Based Advertisement and its Influence on Consumers’ Attitude - Jamalzadeh, Morteza; Behravan, Navid; Masoudi, Roozbeh (International Review of Management and Marketing, 2012)
E-commerce becomes a cornerstone for many businesses over the recent years. Align with e-commerce activities, the marketing communication through online media plays a major role in achieving competitive advantageous. E-mail advertising in this context offers a cost effective, direct and reciprocal means for businesses overcoming time and geographical barriers. As so, this study discussed the advertising e-mail characteristics and its influences on customers’ attitude about email-based advertisement. According to the research findings, entertainment and informativeness of advertising email content is strongly and positively affect customers’ attitude about email-based advertisement. On the other hand, the privacy of advertising e-mail is strongly, yet negatively influences the customers’ attitude towards email-based advertisement. Keywords: Advertising emails; Customers’ attitude; E-commerce; Marketing communication. JEL Classifications: M31; M37